2013
DOI: 10.1021/bi400718r
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Binding of PhoBDBD to Its Cognate DNA Sequence—A Combined Application of Single-Molecule and Ensemble Methods

Abstract: A combined approach based on isothermal titration calorimetry (ITC), fluorescence resonance energy transfer (FRET) experiments, circular dichroism spectroscopy (CD), atomic force microscopy (AFM) dynamic force spectroscopy (DFS), and surface plasmon resonance (SPR) was applied to elucidate the mechanism of protein-DNA complex formation and the impact of protein dimerization of the DNA-binding domain of PhoB (PhoB(DBD)). These insights can be translated to related members of the family of winged helix-turn-heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…[14][15][16][17] Single-molecule fluorescence techniques have emerged as powerful tools for characterization of the kinetics of biosupramolecular interactions [18] and have been successfully applied to study DNA binding with a number of ligands, mainly proteins. [19][20][21] Our FCS study with BBA-OG demonstrated that its association rate constants are in agreement with those reported for typical minor-groove binders, whereas the dissociation rates are much higher. [22][23][24][25] These results suggest that the selectivity of BBA-OG for A/T-rich sites mainly arises from the association process, whereas its low affinity constants result from its high dissociation rate constants, which are several orders of magnitude higher than those of typical minor-groove binders.…”
Section: Introductionsupporting
confidence: 89%
“…[14][15][16][17] Single-molecule fluorescence techniques have emerged as powerful tools for characterization of the kinetics of biosupramolecular interactions [18] and have been successfully applied to study DNA binding with a number of ligands, mainly proteins. [19][20][21] Our FCS study with BBA-OG demonstrated that its association rate constants are in agreement with those reported for typical minor-groove binders, whereas the dissociation rates are much higher. [22][23][24][25] These results suggest that the selectivity of BBA-OG for A/T-rich sites mainly arises from the association process, whereas its low affinity constants result from its high dissociation rate constants, which are several orders of magnitude higher than those of typical minor-groove binders.…”
Section: Introductionsupporting
confidence: 89%
“…Pit does not require chemical energy to drive Pi transport when it is abundant, but when conditions are limiting, the cell uses ATP to scavenge Pi and similar P-containing compounds from the environment via the Pst system. 10 PhoB is a typical winged-helix response regulator that upon aspartyl phosphorylation forms a dimer, which binds in headto-tail arrangement to DNA sequences upstream of Pho regulon genes to recruit RNA polymerase (RNAP) [11][12][13][14] (Fig. 1).…”
Section: The Pho Regulon and Pi Availabilitymentioning
confidence: 99%
“…The recent structural characterization of full-length KdpE, another OmpR/PhoB family member, bound to its direct repeat site confirmed these different domain symmetries while identifying an additional level of asymmetry resulting from intramolecular contacts between the receiver and DNA binding domains within one KdpE subunit (18). Nevertheless, full-length ArcA-P has been reported to form oligomers (19), as have both the isolated N-terminal and C-terminal domains (16), suggesting that although the minimal DNA binding unit is likely a dimer, as demonstrated for PhoB and OmpR (2022), oligomerization beyond a dimer may explain binding to multiple direct repeats.…”
Section: Introductionmentioning
confidence: 99%